Efektivitas Metode Baghdadiyah Pada Anak-Anak Di Desa Purba Sinomba - Abdi Kurniawan; Sandy Futra; Sopia Wulandari; Fazilah Fazilah; Yudiah Yudiah; AKhiruddin Nasution; Sandrina Sandrina; Delvi Wulandari; Efrika Noviyanti Lase (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research aims to assess the extent to which the Bagdadiyah method is effective in community service situations. The Bagdadiyah method, which originates from the legacy of Islamic education, has been applied in various community development programs. This research involved various individuals from various communities who were involved in this KKN service effort.This research method uses the Participation Action Research (PAR) method. The results of this service research show that the Bagdadiyah method has great potential to increase children's understanding of social, moral and cultural values ​​through this method. Furthermore, data analysis also shows that there are several obstacles that require resolution in implementing the Bagdadiyah method. Therefore, this study also suggests steps to further improve the implementation of the Bagdadiyah method.